THE FAILED INSTITUTIONALIZATION OF GENDER EQUALITY UNDER LOCAL ELITE CAPTURE IN VILLAGE GOVERNANCE STRUCTURES - Hartika Arbiyanti; Afgan Fadilla; Surfian Rahmat AP; Fullah Jumaynah; Chomariyana Kartika Hesti (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The decentralization of village governance is expected to create inclusive democratic spaces and promote gender equality at the grassroots level. However, these normative ideals frequently collide with the reality of local power dynamics. Based on a critical literature review, this article investigates how local elite capture and rent-seeking motives hijack gender mainstreaming policies in village governance. The study finds that in the planning phase (Musrenbangdes), women's participation is reduced to "false inclusion" a mere administrative checklist to fulfill requirements for the release of Village Funds, while their strategic proposals are systematically ignored. This exclusion smoothly paves the way for local elites to massively divert the village budget (APBDes) into capital-intensive physical infrastructure projects. This budget hijacking is driven by rent-seeking opportunities and financial kickbacks for elite networks, leaving women's empowerment and human development programs severely underfunded. Ultimately, this study concludes that without strict structural oversight and the active strengthening of women's independent political agency, gender equality in village governance will remain an empty document serving only to preserve local oligarchic power..